UJI KEPRAKTISAN INSTRUMEN EVALUASI BERORIENTASI HIGHER ORDER THINKING SKILL (HOTS) MELALUI MEDIA EDUCAPLAY - Roro Diah Pamungkas; Ina Agustin; Badri Atul Fikriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to measure the practicality of Higher Order Thinking Skills (HOTS)-based evaluation instruments developed through the Educaplay platform in IPAS learning for fifth-grade elementary school students. In the digital era and with the implementation of the Merdeka Curriculum, teachers are required to provide evaluations that not only measure basic knowledge but also stimulate students' critical and analytical thinking skills. Educaplay was chosen because it offers interactive exercise features that can support the creation of engaging and easily accessible HOTS questions. This study employs a quantitative descriptive approach with data collection techniques through a practicality questionnaire administered to teachers and students. The practicality test results showed that the instrument was rated as very practical by teachers at 94% and by students at 91%, with an overall average of 92%. These findings indicate that the HOTS-based evaluation instrument using the Educaplay platform is easy to use, efficient in implementation, and engaging and adaptive for users in the elementary school environment. In conclusion, the Educaplay media has a very good level of practicality and can be an alternative digital evaluation media that meets the demands of 21st-century learning. This media has the potential to support student engagement in evaluation and facilitate teachers in managing competency-based assessment.